Analysis Of White Jellyfish (Aurelia Aurita) Processing Business In CV. Almahaera In Puupi Village Of Kolono Districct Of South Konawe Regency - Ayu Putri Wahyuningsih; Sarinah Sarinah; Muhammad Syukri (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This research aims to find out the process analysis of white jellyfish (aurelia aurita) processing business in cv. almahaera in puupi village of kolono districct of south konawe regency. Determination of the location of the study is done intentionally (purposive). Data collection is done by observation, interview and documeation methods. Respondents in the study were business owners, secretaries and several employees at jellyfish processing companies (Aurelia aurita). The study was analyzed using income analysis. The results showed that the variable total cost of production was produced by a production value of Rp957,435,000, total receipts of Rp2,430,400,000, total revenue of Rp 1,472,965,000 and R/C Ratio of 2.54.